INNOVATIVE BANKING SERVICES IN WORLD COUNTRIES ACCORDING TO INCOME - Makhmudova Mukhlisa Kodirjon kizi (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study analyzes the development trends of innovative banking services, with a focus on the implementation of digital banking across countries categorized by income level. The research aims to examine the disparity in digital banking service advancements between high-income, upper-middle-income, and lower-middle-income countries, identifying underlying causes and opportunities for improvement. Methods: The study employs methods such as induction, deduction, and synthesis, supported by official statistical data from the World Bank and International Monetary Fund. The analysis covers the period from 2014 to 2021, focusing on specific years within this timeframe, and evaluates the global economy, high-income countries (HIC), upper-middle-income countries (UMC), and lower-middle-income countries (LMC). Results: The findings indicate that high-income countries have made substantial progress in digital banking, with nations such as Sweden, Norway, and the Netherlands nearing a cashless economy. Upper-middle-income countries show significant improvement in recent years, while lower-middle-income countries face challenges due to a strong informal economy, limited scientific development, and high corruption levels. Novelty: This study highlights the correlation between economic classification and digital banking adoption. It emphasizes the untapped potential in middle-income countries, suggesting opportunities for expanding digital banking services despite structural challenges, thus providing actionable insights for stakeholders in digital banking innovation.